Late Venous Thromboembolism Prophylaxis after Craniotomy in Acute Traumatic Brain Injury. Issue 2 (February 2015) - Daley, Mitchell J.; Ali, Sadia; Brown, Carlos V. R.
The objective of this study is to compare rates of venous thromboembolism (VTE) in patients who receive enoxaparin prophylaxis compared with no enoxaparin prophylaxis after craniotomy for traumatic brain injury (TBI). This retrospective cohort evaluated all trauma patients admitted to a Level I trauma center from January 2006 to December 2011 who received craniotomy after acute TBI. Patients were excluded if developed VTE before administration of enoxaparin or they died within the first 72 hours of hospital admission. A total of 271 patients were included (enoxaparin prophylaxis, n = 45; no enoxaparin prophylaxis, n = 225). The median time until enoxaparin initiation was 11 ± 1 days. There was no significant difference in the proportion of patients who developed a VTE when using enoxaparin prophylaxis compared with no enoxaparin prophylaxis (2 vs 4%; P = 0.65). Rates of deep vein thrombosis (2 vs 3%; P = 0.87) and pulmonary embolism (0 vs 1%; P = 0.99) were similar between treatment groups, respectively. Late enoxaparin prophylaxis did not demonstrate a protective effect for VTE. Given the overall low event rate, the administration of pharmacologic prophylaxis against VTE late in the treatment course may not be routinely warranted after craniotomy for acute TBI. Further investigation with early administration of enoxaparin is needed.